Modulating the Charge Transport in 2D Semiconductors via Energy‐Level Phototuning. Issue 39 (12th August 2019) - Qiu, Haixin; Zhao, Yuda; Liu, Zhaoyang; Herder, Martin; Hecht, Stefan; Samorì, Paolo
Abstract: The controlled functionalization of semiconducting 2D materials (2DMs) with photoresponsive molecules enables the generation of novel hybrid structures as active components for the fabrication of high‐performance multifunctional field‐effect transistors (FETs) and memories. This study reports the realization of optically switchable FETs by decorating the surface of the semiconducting 2DMs such as WSe2 and black phosphorus with suitably designed diarylethene (DAE) molecules to modulate their electron and hole transport, respectively, without sacrificing their pristine electrical performance. The efficient and reversible photochemical isomerization of the DAEs between the open and the closed isomer, featuring different energy levels, makes it possible to generate photoswitchable charge trapping levels, resulting in the tuning of charge transport through the 2DMs by alternating illumination with UV and visible light. The device reveals excellent data‐retention capacity combined with multiple and well‐distinguished accessible current levels, paving the way for its use as an active element in multilevel memories. Abstract : Optically switchable field‐effect transistors (FETs) are realized by decorating the surface of 2D WSe2 and black phosphorene with photochromic diarylethenes. Both electron and hole transport can be efficiently and reversibly modulated as a result of light irradiation at different wavelengths. These FETs also show five distinguishable output current levels with high‐accuracy readout, demonstrating their huge potential for multilevel memories.